Predictors for venous sinus stent retreatment in patients with idiopathic intracranial hypertension. (13th December 2016) - El Mekabaty, Amgad; Obuchowski, Nancy A; Luciano, Mark G; John, Seby; Chung, Charlotte Y; Moghekar, Abhay; Jones, Stephen; Hui, Ferdinand K
Abstract : Background: Venous sinus stenting for dural sinus stenoses is an emerging alternative to cerebrospinal fluid diversion in cases of medically refractory idiopathic intracranial hypertension. Juxta-stent 're-stenoses' have been reported and managed alternatively with ventricular shunting or stent revision. Identification of factors that might predispose patients to recurrent narrowing may help to select or exclude patients with idiopathic intracranial hypertension for venous sinus stenting. Methods: We retrospectively reviewed a prospectively maintained database spanning December 2011 to May 2015 of all patients with idiopathic intracranial hypertension who were screened for possible venous sinus stenting, including only patients who received a stent, noting symptomatic improvements, changes in opening lumbar puncture pressure, demographic characteristics, and any subsequent intervention after stent placement. Fisher's exact test and logistic regression were used to test each of seven potential predictors for retreatment. Results: There were eight revisions in 31 patients (25.8%). Among Caucasians, 8.0% required a revision compared with 100% of African-Americans (p<0.001). The c-index for race was 0.857. Body mass index (BMI) was also a significant predictor of revision (p=0.031): among class III obese patients the revision rate was 46.2% compared with 16.7% among class I and II obese patients and 0% among overweight to normal weight patients. Conclusions: BMI was a significant predictor of revision, suggesting that higher BMI may have a higher risk of revision. The small number of African-Americans in the study makes interpretation of the practical significance of the revision rate in these patients uncertain. None of the other studied factors was statistically significant.